Validation of the Soil and Water Assessment Tool (SWAT) in Ungauged Catchment - Chen, Lei; Li, Shuang; Wang, Guobo; Xu, Jiajia; Shen, Zhenyao (Journal of Environmental Accounting and Management, 2026)
Measured flow and water quality data play important roles in the application of watershed models, and scarcity data become a key barrier for modeling studies, especially for non-point source pollution simulations. This study focused on the impacts of missing measured data on flow and non-point source pollution simulations by using the Soil and Water Assessment Tool. Both the missing rate and missing location of measured flow and total phosphorus were analyzed and discussed. And the extrapolation of parameters to ungauged catchment was discussed in a typical watershed in the Three Gorges Reservoir Area, China. The results showed that an increasing missing rate would cause worse model performance especially in wet periods. Moreover, the calibrated watershed model could be used in ungauged catchment within an extrapolation idea, but the extrapolation of nonpoint source predictions showed poor perfor-mance. This study also indicated that watershed model could be used for ungauged catchment simulation if similar environments and other hu-man disturbance do not exist. This paper provides new guides for water quality monitoring and the usage of watershed models during ungauged periods.